1983
DOI: 10.1073/pnas.80.18.5772
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a proenkephalin-like precursor in amphibian brain.

Abstract: The mammalian proenkephalin-derived peptides [Leu]enkephalin, [Metlenkephalin, and [Met]enkephalin-Arg6-Phe7 were identified in acid extracts of the brain of Bufo marinus by using reversed-phase HPLC and specific radioimmunoassays.[Met]Enkephalin was the predominant opioid peptide present (270 pmol/g). In contrast, the octapeptide [Met]enkephalin-Arg6-Gly7-Leu8, which is also derived from mammalian proenkephalin, was not detected. The ratio of free [Met]enkephalin to [Met]enkephalin-Arg6-Phe7 was found to be 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1987
1987
2004
2004

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(11 citation statements)
references
References 33 publications
(38 reference statements)
1
10
0
Order By: Relevance
“…Evidently, in the lines giving rise to modern mammals and amphibians, there have been substitutions of Leu for Met in one of the enkephalin species and of Tyr for Leu in the octapeptide variant. These observations are based on gene sequences but are compatible with reports that Met-enkephalin Arg6Gly7Leus is absent from extracts of the brain of Bufo marinus (195). Extracts of Bufo brain do, however, contain Leu-enkephalin, which presumably arises from prodynorphin and is consistent with the observation of other prodynorphin-related peptides in amphibia (63).…”
Section: Sequences and Genessupporting
confidence: 90%
“…Evidently, in the lines giving rise to modern mammals and amphibians, there have been substitutions of Leu for Met in one of the enkephalin species and of Tyr for Leu in the octapeptide variant. These observations are based on gene sequences but are compatible with reports that Met-enkephalin Arg6Gly7Leus is absent from extracts of the brain of Bufo marinus (195). Extracts of Bufo brain do, however, contain Leu-enkephalin, which presumably arises from prodynorphin and is consistent with the observation of other prodynorphin-related peptides in amphibia (63).…”
Section: Sequences and Genessupporting
confidence: 90%
“…When these studies were begun in the 1980s, it was assumed that: (a) met-enkephalin and leu-enkephalin would be co-localized in neurons; (b) the molar ratio of metenkephalin to leu-enkephalin in CNS extracts would be approximately 4:1; and (c) both of these opioids would be encoded by the same precursor. Steady-state analyses of non-mammalian brain extracts (Kilpatrick et al, 1983;Lindberg & White, 1986), and immunocytochemical studies (Vallarino et al, 1994(Vallarino et al, , 1998 indicated that the evolution of the enkephalinergic system was more complicated than had been anticipated.…”
Section: Proenkephalinmentioning
confidence: 95%
“…In an earlier study, higher than expected levels of met-enkephalin were detected in the brain of B. marinus [17]relative to leu-enkephalin. Subsequent studies have shown that anuran amphibian proenkephalin lacks a leu-enkephalin sequence [18, 19, 20, 21], hence it was assumed that the met-enkephalin present in the brains of anuran amphibians came exclusively from proenkephalin.…”
Section: Discussionmentioning
confidence: 99%